Altered Ca2+-Homeostasis of Cisplatin-Treated and Low Level Resistant Non-Small-Cell and Small-Cell Lung Cancer Cells - Kathrin Schrödl; Hamza Oelmez; Martin Edelmann; Rudolf Maria Huber; Albrecht Bergner (Cellular Oncology)
Background: Chemotherapy often leads to encouraging responses in lung cancer. But, in the course of the treatment, resistance to chemotherapy ultimately limits the life expectancy of the patient. We aimed at investigating if treatment with cisplatin alters the intracellular Ca2+-homeostasis of lung cancer cells and how this may be related to cisplatin resistance.